2020
DOI: 10.1177/1470357220901855
|View full text |Cite
|
Sign up to set email alerts
|

In search of visual expertise: examining skilled vision in the work of news photo professionals

Abstract: Photojournalism professionals play a key role in producing and choosing the visual coverage that we see in the daily news media. This article focuses on photo editors and other photojournalism professionals behind the news images, and explores how they see and look at pictures professionally in order to decide what is newsworthy. The actual work practices of photojournalism professionals were scrutinized by using methods of newsroom observation and interviews at three media organizations. The theoretical frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Photojournalists and editors impact the visual coverage of news and the associated messages. Therefore, what is considered newsworthy is published and influences public opinion (Mäenpää, 2022). The segment of activist photojournalists is interested in the book market to increase their impact on the broader public, or they might only be interested in diversifying their sources of income.…”
Section: Discussionmentioning
confidence: 99%
“…Photojournalists and editors impact the visual coverage of news and the associated messages. Therefore, what is considered newsworthy is published and influences public opinion (Mäenpää, 2022). The segment of activist photojournalists is interested in the book market to increase their impact on the broader public, or they might only be interested in diversifying their sources of income.…”
Section: Discussionmentioning
confidence: 99%
“…Sitä, mikä oikeastaan on "hyvä" valokuva, ei kuitenkaan välttämättä tarkemmin määritellä (Bednarek & Caple 2017, 108). Kuvajournalisteilla on tapana valita samat kuvat "huippukuviksi" toisistaan riippumatta, eli kuvajournalisteilla on jaettu professionaalinen ymmärrys hyvistä kuvista (Mäenpää 2020). Kuvajournalismin tutkijan Jenni Mäenpään (2020, 5) mukaan hyvän uutiskuvan määrittämisessä kuvajournalistit yhdistävät tietämystään uutisarvoista, estetiikasta, yritys-VISUAALINEN JOURNALISMI 245 logiikasta ja ammattietiikasta.…”
Section: Visuaalisen Journalismin Normitunclassified
“…The interviews and observations revealed that the professionals’ alleged knowledge about their clients or audiences does not primarily come from reception research but from their experiences with and perceptions about the behaviour of those groups. It is actually a part of the photojournalism professionals’ expertise to monitor the behaviour of the clients or audiences and learn from it (Mäenpää, 2020: 9).…”
Section: Shared Ethics: People’s Right To Know Versus Respecting the ...mentioning
confidence: 99%